Artificial Reproduction of Blue Bream (Ballerus ballerus L.) as a Conservative Method under Controlled Conditions - Przemysław Piech; Roman Kujawa (Animals, 2021)
The blue bream Ballerus ballerus (L.) is one of two species of the Ballerus genus occurring in Europe. The biotechnology for its reproduction under controlled conditions needs to be developed to conserve its local populations. Therefore, a range of experiments were performed to obtain valuable gametes from blue bream following hormonal stimulation with carp pituitary homogenate (CPH), Ovopel and Ovaprim. CPH and Ovopel were injected twice and Ovaprim—once, under a pectoral fin. The spawners were inspected 12 h after the last injection, and the gametes were collected. Eggs were collected from spawning females and fertilized with sperm from three males. The smallest number of ovulating blue bream (four females) was obtained from individuals stimulated with Ovaprim. There were six to nine ovulating females in the other groups, accounting for 60–90% of the females in the respective groups. The latency period was the shortest in the spawners stimulated with Ovopel. The fish in this group ovulated 14 h after the hormonal injection. Spawning was synchronized and all females spawned simultaneously. The highest average weight of eggs per fish (75.4 g) was obtained from the females stimulated with Ovopel, whereas the individuals stimulated with Ovaprim provided the smallest average amount of eggs (49.5 g). The study showed that blue bream spawners are not very sensitive to reproduction-related handling under controlled conditions.